Species-rich and polyploid-poor: Insights into the evolutionary role of whole-genome duplication from the Cape flora biodiversity hotspot - Oberlander, Kenneth C; Dreyer, Léanne L; Goldblatt, Peter; Suda, Jan; Linder, H Peter (American journal of botany, 2016)
PREMISE OF THE STUDY: Whole-genome duplication (WGD) in angiosperms has been hypothesized to be advantageous in unstable environments and/or to increase diversification rates, leading to radiations. Under the first hypothesis, floras in stable environments are predicted to have lower proportions of polyploids than highly, recently disturbed floras, whereas species-rich floras would be expected to have higher than expected proportions of polyploids under the second. The South African Cape flora is used to discriminate between these two hypotheses because it features a hyperdiverse flora predominantly generated by a limited number of radiations (Cape clades), against a backdrop of climatic and geological stability. METHODS: We compiled all known chromosome counts for species in 21 clades present in the Cape (1653 species, including 24 Cape clades), inferred ploidy levels for these species by inspection or derived from the primary literature, and compared Cape to non-Cape ploidy levels in these clades (17,520 species) using G tests. KEY RESULTS: The Cape flora has anomalously low proportions of polyploids compared with global levels. This pattern is consistently observed across nearly half the clades and across global latitudinal gradients, although individual lineages seem to be following different paths to low levels of WGD and to differing degrees. CONCLUSIONS: This pattern shows that the diversity of the Cape flora is the outcome of primarily diploid radiations and supports the hypothesis that WGD may be rare in stable environments.
Keywords: Biodiversity; Jihoafrická republika; polyploidy; zeměpis; genom rostlinný; Genome, Plant; South Africa; whole-genome duplication; diversification; biodiverzita; ploidie; biologická evoluce; environmental stability; Geography; Cape flora; evolutionary radiation; Biological Evolution; Magnoliopsida; Polyploidy; Ploidies; polyploidie